2020
DOI: 10.4103/njms.njms_10_19
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral mandibular condyle fractures: Should we open both?

Abstract: Bilateral condylar fractures are common but are frequently undertreated. In most of the cases, only one side is surgically addressed and the other side is managed conservatively. Bilateral condylar fractures lead to loss of ramal height bilaterally, accentuated anterior open bite, disruption of articular surfaces, and disc and muscle attachments. In a mandibular bilateral condylar fracture, even though open reduction and internal fixation (ORIF) is done on one side, a patient still needs Inter Maxillary Fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although many studies have suggested ORIF for BCF in adult patients, this was not the case for children, as cases reported in the literature suggest that conservative treatment should be the first‐line choice for pediatric patients 22 . The result of the present case is consistent with those reported in the literature, in which the conservative approach was chosen for many reasons, including patient age and medical condition as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have suggested ORIF for BCF in adult patients, this was not the case for children, as cases reported in the literature suggest that conservative treatment should be the first‐line choice for pediatric patients 22 . The result of the present case is consistent with those reported in the literature, in which the conservative approach was chosen for many reasons, including patient age and medical condition as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of these complications is considered to be great. The majority of the cases of ankylosis were caused by unreplaced nonsurgically treated condyles [12].…”
Section: Discussionmentioning
confidence: 99%
“…Condylar fractures may be isolated unilateral or bilateral fractures or could present concomitantly with other maxillofacial injuries [1]. Approximately 40% to 50 % of condylar fractures are bilateral [2]. Despite this high prevalence, the management is controversial at best due to different schools of thought and a lack of consensus among surgeons worldwide.…”
Section: Introductionmentioning
confidence: 99%